Membangun Kreativitas Anak melalui Kegiatan Menggambar dan Mewarnai di Yayasan Al Falah Kemayoran - Fahriana Nur Anita; Adela Karmelita Sari; Nafis Laelatullaena (Universitas 17 Agustus 1945 Semarang, Indonesia, 2024)
Empowerment activities at the Al Falah Kemayoran Foundation are a positive step in improving the quality of life of disadvantaged children. This article reflects an introduction to empowerment innovations through drawing, coloring and general knowledge questions and answers in orphanages. The activity implementation method involves a training and mentoring approach, by providing theory, direct practice, and question and answer sessions. The results of the drawing and coloring activities show the participants' success in carrying out these activities neatly. Meanwhile, general knowledge question and answer activities also went well, showing the children's active participation. During the activity, the empowerment team aims to make a positive contribution by increasing the skills, knowledge and creativity of orphanage children. Material assistance, providing new skills, and creating a positive environment are the focus of the team. Awareness of the need for donations and support from the community was also raised as an important aspect. The conclusion of this activity emphasizes that through collaboration between the orphanage, the empowerment team, and the community, an environment that supports the development of orphaned children can be created. Financial and material support is a key factor in ensuring the education and welfare of children at the Al Falah Kemayoran Foundation. Thus, this empowerment activity can be considered a positive step in creating changes that have an impact on the quality of life of children in orphanages.